STRUCTURAL SYNTHESIS OF HYBRID NEURAL NETWORKS ENSEMBLES - Sineglazov, V. M.; Chumachenko, O. I.; Bedukha, O. R. (Electronics and Control Systems, 2018)
It is considered the structural synthesis of hybrid neural networks ensembles. It is chosen the ensemble topology as parallel structure with united layer. It is developed a hybrid algorithm for the problem solution which includes some algorithms preliminary choice of classifiers(modules of neural networks-hybrid neural networks, which consist of Kohonen, basic neural networks and bi-directional associative memory), creation the bootstrap training samples for every classifier, training these classifiers, optimal choice of necessity ones, determination of layer union weight coefficients, ensemble pruning. For the solution of optimal choice classifiers it is used two criteria: accuracy and variety.